Optimization of the depressurization rate and stepwise strategy for hydrate exploitation using a genetic algorithm-based depressurization method. (16th January 2023) - Ge, Kun; Zhang, Xinyu; Wang, Jiaqi; Cheng, Chuanxiao; He, Jiale
Highlights: Numerical simulation of gas production by stepwise depressurization is presented. The depressurization rate is optimized by genetic algorithm. The configuration strategies of stepwise depressurization are optimized. The exploitation efficiency has been improved. Abstract: Depressurization is one of the most effective methods for hydrate exploitation. Optimization of the pressure-drop strategy for improving the exploitation efficiency requires immediate attention. In this study, a hydrate decomposition model was for the first time combined with a genetic algorithm. The pressure-drop rate and strategy were optimized based on the exploitation efficiency. The depressurization rate of the continuous slow depressurization method was optimized. Subsequently, the best pressure-drop rate for stepwise depressurization was hypothesized and validated. In addition, the stepwise strategy was optimized. For the two depressurization methods, increasing the pressure-drop rate increased the exploitation efficiency, while increasing the number of pressure-drop stages in the stepwise depressurization method adversely impacted the exploitation efficiency. Prolonged constant-pressure intervals reduced the efficiency when there were few pressure-drop stages; however, the opposite trend emerged for a high number of depressurization steps. This study provides guidance for optimizing the production efficiency of hydrate exploitation via depressurization.